2021
DOI: 10.1007/s12209-021-00284-w
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Conversion of Biomass-Derived Furancarboxylic Acids with Retention of Carboxylic Acid Moiety

Abstract: Catalytic reduction systems of 2-furancarboxylic acid (FCA) and 2,5-furandicarboxylic acid (FDCA) with H2 without reduction of the carboxyl groups are reviewed. FCA and FDCA are produced from furfural and 5-hydroxymethylfurfural which are important platform chemicals in biomass conversions. Furan ring hydrogenation to tetrahydrofuran-2-carboxylic acid (THFCA) and tetrahydrofuran-2,5-dicarboxylic acid (THFDCA) easily proceeds over Pd catalysts. Hydrogenolysis of one C–O bond in the furan ring produces 5-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 116 publications
0
22
0
Order By: Relevance
“…157,158 Upgrading of LA to γ-valerolactone (GVL), which plays a central role in the biomass-based carbon cycle, is the most classical reaction. 157,159 In 2013, Mika and co-workers described the synthesis of GVL in a continuousflow reactor with various heterogeneous catalysts (10% Pd/C, 5% Ru/C, and Raney Ni CatCart) and found that the Raney Ni catalyst resulted in activity lower than that of Ru/C. 160 Later, Rong and co-workers investigated the same reaction and compared the RQ Ni with the normal Raney Ni catalyst.…”
Section: Glycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…157,158 Upgrading of LA to γ-valerolactone (GVL), which plays a central role in the biomass-based carbon cycle, is the most classical reaction. 157,159 In 2013, Mika and co-workers described the synthesis of GVL in a continuousflow reactor with various heterogeneous catalysts (10% Pd/C, 5% Ru/C, and Raney Ni CatCart) and found that the Raney Ni catalyst resulted in activity lower than that of Ru/C. 160 Later, Rong and co-workers investigated the same reaction and compared the RQ Ni with the normal Raney Ni catalyst.…”
Section: Glycerolmentioning
confidence: 99%
“…Levulinic acid (LA), which can be simply obtained via acid-catalyzed dehydration of carbohydrates, is another vitally important platform chemical and has been widely used as a substrate for the synthesis of value-added chemicals and fuels in recent years. , Upgrading of LA to γ-valerolactone (GVL), which plays a central role in the biomass-based carbon cycle, is the most classical reaction. , In 2013, Mika and co-workers described the synthesis of GVL in a continuous-flow reactor with various heterogeneous catalysts (10% Pd/C, 5% Ru/C, and Raney Ni CatCart) and found that the Raney Ni catalyst resulted in activity lower than that of Ru/C . Later, Rong and co-workers investigated the same reaction and compared the RQ Ni with the normal Raney Ni catalyst.…”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 99%
“…have been obtained by the functionalization/ defunctionalization of hydroxyl or/and aldehyde groups with different catalytic systems [41]. Hydrodeoxygenation or acidolysis of the furan ring can produce alkanes, alcohols, furancarboxylic acids, LA, or γ-valerolactone (GVL) [42,43]. During all these transformations, catalysts are vitally important in improving yield and selectivity.…”
Section: Catalytic Upgrading Of Hmfmentioning
confidence: 99%
“…Similar to the glucose to HMF conversion mentioned above, xylose can be transformed into furfural via Lewis acid-catalyzed isomerization followed by Brønsted acid-catalyzed dehydration (Scheme 5) [108,109]. Since pristine MIL-101(Cr), limited by its relatively low Brønsted acidity, only displayed unsatisfied catalytic performance in the application of xylose to furfural transformation, several types of MIL-101(Cr)-based materials with dual-acid sites were developed to promote catalytic conversion.…”
Section: Xylose To Furfuralmentioning
confidence: 99%